Precision Nutrient and Soil Tillage Management for Sustainable Winter Barley Production (Hordeum vulgare L.) and Tillage Impact on Soil CO2 Emission - Amare Assefa Bogale; Zoltan Kende; Akos Tarnawa; Peter Miko; Marta Birkás; Gergő Péter Kovács; Attila Percze (Agronomy)
Precision sustainable agronomic practices are crucial for achieving global food security as well as mitigating climate change. A field experiment was conducted at the Hungarian University of Agriculture and Life Sciences in Gödöllő from 2023 to 2024. The study aimed to evaluate the effects of soil tillage and foliar nutrient supplementation on winter barley yield, associated characteristics, and soil CO2 emissions. Employing a split-plot design with three replications, the experiment included four nutrient treatments (control, bio-cereal, bio-algae, and MgSMnZn blend) and two soil tillage type (i.e., plowing and cultivator). The study found that soil CO2 emissions were influenced by the crop growth stage across both tillage treatments throughout the growing seasons, but the tillage system itself did not have an effect. Similarly, the leaf chlorophyll content was not affected by tillage and nutrient treatments. Plant height, the leaf area index (LAI), and thousand kernel weights (TKW) were significantly affected by nutrient treatments across the growing seasons. Both nutrient and tillage treatments also had a notable effect on the number of productive tillers in winter barley. Moreover, nutrient and tillage treatments consistently influenced grain yield across the two growing seasons, and their interaction significantly impacted both grain yield and thousand kernel weights. The bio-cereal nutrient treatment combined with plowing tillage yielded the highest values for most parameters throughout the growing seasons. Therefore, it can be concluded that the combination of bio-cereal nutrient treatments and plowing tillage can boost winter barley yields. Notably, soil CO2 emissions peak during the crops’ reproductive stage, surpassing levels from early growth.